Neutral electrolyte for aluminum-air battery, preparation method and application thereof

CN123018260APending Publication Date: 2026-10-30NINGBO ALUMINUM NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611326627.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0010]鉴于以上现有技术的不足之处,本发明提供了一种铝空气电池用中性电解液及其制备方法和应用,以解决传统中性铝空气电池中氢氧化铝产物在阳极表面致密粘附、导致放电电压快速跌落及高电流密度下电池失效的技术问题,同时规避碱性电解液强腐蚀、高析氢的安全缺陷

Benefits of technology

[0025]本发明铝空气电池用中性电解液,通过创新性地将A组分(羟基羧酸金属盐)和B组分(聚合态无机铝盐)复配作为复合添加剂,不仅实现了对铝阳极放电产物氢氧化铝原位抑制和静电排斥分散的双重协同调控,而且实现了在宽电流密度范围内(1~5 mA/cm2)长期稳定的高放电电压平台。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018260A_ABST
    Figure CN123018260A_ABST
Patent Text Reader

Abstract

The application discloses a neutral electrolyte for an aluminum-air battery, which comprises a base electrolyte, a composite additive and a solvent; the composite additive is composed of an A component and a B component; the A component is a solid powder or an aqueous solution of a hydroxyl carboxylic acid metal salt; and the B component is a polymeric inorganic aluminum salt. The neutral electrolyte of the application realizes the dual regulation of in-situ inhibition and electrostatic repulsion dispersion of the discharge product of the aluminum anode, i.e. aluminum hydroxide, through the synergistic cooperation of the A component and the B component, realizes a long-term stable high discharge voltage platform in a wide current density range, effectively inhibits the adhesion of the anode product, and significantly improves the effective specific energy. The application further discloses a preparation method and application of the neutral electrolyte for the aluminum-air battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of aluminum-air batteries, and more particularly to a neutral electrolyte for aluminum-air batteries, its preparation method, and its application. Background Technology

[0002] Aluminum-air batteries, using metallic aluminum as the anode and oxygen from the air as the cathode reactant, possess significant advantages such as high theoretical specific energy, abundant resources, low cost, and good safety, making them one of the ideal choices for next-generation energy storage technologies. Among these, systems using neutral salt solutions (such as sodium chloride and potassium chloride) as electrolytes have attracted considerable attention due to their lack of strong corrosiveness, low requirements for the operating environment, and greater suitability for consumer-grade products.

[0003] However, neutral aluminum-air batteries face a core bottleneck in practical applications: during discharge, the aluminum anode continuously dissolves, generating aluminum ions (Al). 3+ These aluminum ions readily combine with hydroxide ions in water in a neutral environment, forming insoluble, insulating aluminum hydroxide (Al(OH)3) colloids or precipitates in situ on the anode surface. As discharge progresses, these products accumulate on the electrode surface, forming a dense passivation film that severely clogs the electrode reaction interface, increases the battery's internal resistance, and causes a sharp drop in discharge voltage, resulting in a rapid decline in battery performance within a short period. Furthermore, the electrolyte becomes viscous due to product accumulation, further hindering ion transport.

[0004] To address the above problems, existing technologies are mainly improved in the following directions:

[0005] One approach is to modify the surface of the aluminum anode. For example, the patent with authorization announcement number CN116190866B adopts a synergistic scheme of "coating an aluminum anode with a porous carbon layer + electrolyte additives". First, a slurry made of activated carbon, carbon black, PVDF binder, etc. is coated on the surface of the aluminum sheet. After drying, a porous carbon layer is formed. At the same time, sodium carboxymethyl cellulose (CMC) is added to the sodium chloride electrolyte. However, this scheme has a complex process and high cost. It requires additional steps such as slurry preparation, coating, and drying. The production process is long and the yield control is difficult, making it unsuitable for large-scale mass production. Moreover, the final discharge voltage is only about 0.6 V and the capacity is less than 750 mAh / g, resulting in low overall performance.

[0006] Secondly, a metal salt composite additive is added to the electrolyte. Patent CN117335060A describes a composite additive formed by adding indium chloride and gallium chloride to a sodium chloride aqueous solution. This utilizes the properties of In and Ga elements to disrupt the aluminum surface oxide film, activate the aluminum anode, and simultaneously increase the hydrogen evolution overpotential to suppress self-corrosion. However, this system only focuses on activating the anode to increase the initial discharge voltage, without effectively controlling the adhesion and accumulation of aluminum hydroxide products, thus failing to solve the electrode passivation problem under long-term discharge. Furthermore, it only verifies short-term discharge performance within 2 hours, lacking long-term service data to support its effectiveness.

[0007] Thirdly, an iron-activated electrolyte is used. Patent CN120016029A adds ferric salts as an activating additive to a sodium chloride aqueous solution, utilizing the hydrolysis of iron ions to release protons and destroy the aluminum hydroxide passivation layer on the aluminum anode surface. However, this system relies on acidification of the interface to destroy the passivation layer, inevitably leading to the side effect of increased hydrogen evolution due to aluminum self-corrosion. Higher concentrations result in greater voltage fluctuations and lower anode utilization, making it impossible to simultaneously achieve a balance between high voltage and low self-corrosion.

[0008] In addition, there is a solution that uses sodium chloride neutral electrolyte combined with organic corrosion inhibitors such as tea tree oil, amino acids, and sugars (publication number CN113851665A). However, the protective film formed by a single organic component is relatively thin, aluminum anode products still adhere in large quantities, the discharge voltage fluctuates greatly, the long-term endurance performance is poor, and there is a lack of long-term voltage stabilization capability.

[0009] In summary, existing neutral electrolyte technologies struggle to simultaneously achieve both a "high and stable discharge voltage plateau" and "extremely low anolyte adhesion rate." While corrosion-inhibiting additives can maintain voltage, they may exacerbate product adhesion to the surface, leading to a rapid voltage drop in the mid-to-late stages. Dispersing / activating additives, while reducing product coverage or breaking passivation, often come at the cost of sacrificing discharge stability and accelerating corrosion. Furthermore, most existing technologies have only validated a voltage of 1 mA / cm². 2 Performance at extremely low current densities, with current increased to 5 mA / cm². 2 It then rapidly passivates and fails; moreover, the discharge voltage decays quickly, and a large portion of the capacity falls into the ineffective range below 0.8 V, resulting in extremely low effective specific energy that can actually be utilized by the load. Summary of the Invention

[0010] In view of the shortcomings of the prior art, the present invention provides a neutral electrolyte for aluminum-air batteries, its preparation method and application, to solve the technical problems of dense adhesion of aluminum hydroxide products on the anode surface in traditional neutral aluminum-air batteries, which leads to rapid drop in discharge voltage and battery failure under high current density, while avoiding the safety defects of strong corrosion and high hydrogen evolution of alkaline electrolytes.

[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0012] A neutral electrolyte for aluminum-air batteries, the electrolyte comprising a base electrolyte, a composite additive, and a solvent; the composite additive is composed of a compound of component A and component B.

[0013] Component A is a solid powder / particle or aqueous solution of a metal salt of hydroxycarboxylic acid;

[0014] Component B is a polymeric inorganic aluminum salt.

[0015] As a preferred technical solution, the hydroxycarboxylic acid metal salt in component A is an alkali metal salt and / or a transition metal salt of lactic acid.

[0016] As a preferred technical solution, component A is at least one of sodium lactate, potassium lactate, zinc lactate, and lithium lactate.

[0017] As a preferred technical solution, component B is at least one of polyaluminum chloride, polyaluminum sulfate, polyaluminum ferric silicate, and polyaluminum ferric chloride.

[0018] As a preferred technical solution, component A is sodium lactate; and component B is polyaluminum chloride.

[0019] As a preferred technical solution, based on the total volume of the neutral electrolyte for the aluminum-air battery, the amount of component A added is 0.03–3 g / L (based on the effective mass of the hydroxycarboxylic acid metal salt), and the amount of component B added is 0.05–5 g / L.

[0020] As a preferred technical solution, the basic electrolyte is sodium chloride and / or potassium chloride.

[0021] As a preferred technical solution, the content of the basic electrolyte is 1 to 3 mol / L, based on the total weight of the neutral electrolyte for the aluminum-air battery.

[0022] Another aspect of the present invention is to provide a method for preparing the neutral electrolyte for aluminum-air batteries as described above, the method comprising the following steps: adding component A and component B to an aqueous solution of a basic electrolyte, stirring until homogeneous or dissolving by ultrasonication, thereby obtaining the neutral electrolyte for aluminum-air batteries.

[0023] Another aspect of the present invention is to provide an application of a neutral electrolyte for an aluminum-air battery, wherein the neutral electrolyte for an aluminum-air battery as described above is added to an aluminum-air battery cavity composed of an anode aluminum plate and a cathode plate to obtain an aluminum-air battery.

[0024] The beneficial effects of this invention are:

[0025] This invention provides a neutral electrolyte for aluminum-air batteries. By innovatively combining component A (a metal hydroxycarboxylic acid salt) and component B (a polymerized inorganic aluminum salt) as a composite additive, it achieves not only synergistic regulation of in-situ suppression and electrostatic repulsion dispersion of aluminum hydroxide, the aluminum anolyte discharge product, but also enables operation over a wide current density range (1–5 mA / cm²). 2 A long-term stable high discharge voltage platform.

[0026] Specifically, component A can form a stable, soluble aluminum lactate complex with the aluminum ions generated during discharge, inhibiting the in-situ formation of aluminum hydroxide on the electrode surface from the source and preventing the formation of the initial passivation layer. Component B, as a positively charged inorganic polymer, preferentially adsorbs onto the surface of the already formed aluminum hydroxide particles, preventing their deposition and aggregation on the anode surface through electrostatic repulsion. Components A and B work synergistically through the above complementary mechanisms, fundamentally solving the failure problem of neutral aluminum-air batteries caused by product adhesion at high current densities.

[0027] Experimental verification has shown that the present invention achieves the following outstanding beneficial effects compared with the prior art:

[0028] 1) Extremely low anodic product adhesion rate: The proportion of aluminum adhering to the anode can be reduced to as low as 0.66%, which is far lower than the 13.18% of the blank group, effectively avoiding the blockage and passivation of the electrode interface.

[0029] 2) Excellent discharge stability and high voltage plateau: at 1 mA / cm 2 After 90 hours of continuous discharge, the voltage remained at 1.28 V, and the discharge curve was almost a horizontal straight line with no fluctuations or attenuation; at 5 mA / cm 2 After continuous discharge for 90 hours at high current density, the voltage remained above 1.15 V, with a stable voltage plateau and no attenuation, successfully overcoming the technical bottleneck of passivation failure of neutral electrolyte under medium current density.

[0030] 3) Significantly improved effective specific energy: Based on the lowest commonly used operating voltage of electronic equipment, 0.8 V, 5 mA / cm 2 The effective specific energy reaches 2323.41 mWh / g, which is 108% higher than the blank group. This significantly improves the actual output usable energy of the battery and effectively solves the industrialization pain point that a large amount of capacity of the existing electrolyte falls into the ineffective low voltage range and the actual range does not meet the standard.

[0031] 4) Simple preparation process and low cost: No complex pretreatment such as coating or modification of aluminum anode is required. It can be achieved simply by adding compound additives to conventional neutral electrolyte. It is suitable for mass production and meets the needs of consumer-grade and portable low-power products. It has extremely high industrialization value.

[0032] In summary, the neutral electrolyte for aluminum-air batteries provided by this invention not only possesses excellent discharge stability, high effective energy density, and extremely low product adhesion rate, but also takes into account the advantages of low self-corrosion, long lifespan, and low cost, thus meeting the stringent requirements for long-term durability and stability in scenarios such as sensors, low-power devices, and emergency equipment. Attached Figure Description

[0033] Figure 1 Example 1 and Comparative Examples 1-3 of the present invention are at 1 mA / cm 2 Discharge voltage-time curve under constant current density.

[0034] Figure 2 Example 1 and Comparative Examples 1-3 of the present invention were at 5 mA / cm 2 Discharge voltage-time curve under constant current density.

[0035] Figure 3 Examples 1-5 and Comparative Example 1 of the present invention were at 1 mA / cm 2 Discharge voltage-time curve under constant current density.

[0036] Figure 4 Examples 1-5 and Comparative Example 1 of the present invention were at 5 mA / cm 2 Discharge voltage-time curve under constant current density.

[0037] Figure 5 Examples 1, 6-8, and Comparative Examples 1 and 2 of the present invention were performed at 1 mA / cm². 2 Discharge voltage-time curve under constant current density.

[0038] Figure 6 Examples 1, 6-8, and Comparative Examples 1 and 2 of the present invention were performed at 5 mA / cm². 2 Discharge voltage-time curve under constant current density.

[0039] Figure 7 Examples 1, 9-11 and Comparative Examples 1, 3, 4 of the present invention were at 1 mA / cm 2 Discharge voltage-time curve under constant current density.

[0040] Figure 8 Examples 1, 9-11 and Comparative Examples 1, 3, and 4 of the present invention were performed at 5 mA / cm². 2 Discharge voltage-time curve under constant current density. Detailed Implementation

[0041] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.

[0042] Example 1

[0043] This embodiment provides a neutral electrolyte for aluminum-air batteries, formulated as follows: Sodium chloride (23.4 g) is added to 200 mL of deionized water and stirred thoroughly to dissolve, yielding a 2 mol / L sodium chloride basic electrolyte aqueous solution. Then, polyaluminum chloride (equivalent to 0.5 g / L) and sodium lactate (equivalent to 0.3 g / L based on the effective mass of sodium lactate) are added to the above basic electrolyte aqueous solution. The solution is stirred at 300 r / min for 25 min at room temperature until completely dissolved. After standing to remove bubbles, the neutral electrolyte for aluminum-air batteries is obtained. The prepared electrolyte is injected into an anode aluminum plate (high-purity aluminum, 3 mm thick, geometric area 16.6 cm²). 2 (and air cathode sheet (waterproof and breathable carbon paper, loaded with manganese oxide catalyst, geometric area 16.6 cm²)) and air cathode sheet (waterproof and breathable carbon paper, loaded with manganese oxide catalyst, geometric area 16.6 cm²) 2 Aluminum-air battery cells are assembled in the cavity of an aluminum-air battery composed of aluminum and air.

[0044] Example 2

[0045] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, the effective mass-calculated addition amount of sodium lactate is 0.03 g / L.

[0046] Example 3

[0047] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, the effective mass-calculated addition amount of sodium lactate is 3 g / L.

[0048] Example 4

[0049] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, the equivalent addition amount of polyaluminum chloride is 0.05 g / L.

[0050] Example 5

[0051] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, the equivalent addition amount of polyaluminum chloride is 5 g / L.

[0052] Example 6

[0053] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, potassium lactate is used instead of sodium lactate.

[0054] Example 7

[0055] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, zinc lactate is used instead of sodium lactate.

[0056] Example 8

[0057] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, lithium lactate is used instead of sodium lactate.

[0058] Example 9

[0059] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, polyaluminum sulfate is used instead of polyaluminum chloride.

[0060] Example 10

[0061] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, polyaluminum ferrosilicon is used instead of polyaluminum chloride.

[0062] Example 11

[0063] The neutral electrolyte for aluminum-air batteries in this embodiment has the same raw material composition and preparation steps as in Example 1. The difference is that in this embodiment, polyaluminum ferric chloride is used instead of polyaluminum chloride.

[0064] Comparative Example 1

[0065] The neutral electrolyte for aluminum-air batteries in this comparative example has the same raw material composition and preparation steps as in Example 1. The difference is that component A (sodium lactate) and component B (polyaluminum chloride) are not added to the electrolyte in this comparative example, which is a blank experiment.

[0066] Comparative Example 2

[0067] The neutral electrolyte for aluminum-air batteries in this comparative example has the same raw material composition and preparation steps as in Example 1. The difference is that component A (sodium lactate) is not added to the electrolyte in this comparative example; that is, only component B, polyaluminum chloride, is added as a single additive.

[0068] Comparative Example 3

[0069] The neutral electrolyte for aluminum-air batteries in this comparative example has the same raw material composition and preparation steps as in Example 1. The difference is that component B (polyaluminum chloride) is not added to the electrolyte in this comparative example; that is, only component A, sodium lactate, is added as a single additive.

[0070] Comparative Example 4

[0071] The neutral electrolyte for aluminum-air batteries in this comparative example has the same raw material composition and preparation steps as in Example 1. The difference is that polyaluminum silicate sulfate is used instead of polyaluminum chloride in this comparative example.

[0072] Aluminum-air battery cells assembled with the same structure using neutral electrolytes from Examples 1-11 and Comparative Examples 1-4 were subjected to constant current discharge tests. The constant current discharge performance was tested using a Blue Battery testing system. The assembled aluminum-air battery cells were allowed to stand at room temperature (25±2℃) for 0.5 hours until the open-circuit voltage stabilized, and then discharged at 1 mA / cm². 2 and 5 mA / cm 2 The system discharges at a constant current density. A data acquisition system automatically records the voltage-time curves during the discharge process. The following data are also recorded:

[0073] (1) Aluminum consumption: Weigh the aluminum anode before and after discharge and calculate the difference. Calculate the aluminum anode utilization rate, specific capacity, and specific energy.

[0074] (2) Mass of electrode adhesion products: After the discharge is completed, the aluminum anode is removed, the surface is slowly rinsed with deionized water, dried at 80°C for 12 hours, and the mass of aluminum hydroxide adhering to the surface is weighed. .

[0075] (3) Weigh the aluminum plate after the reaction and calculate the total mass of aluminum actually consumed. .

[0076] (4) Calculate the percentage of aluminum adhering to the electrode according to the formula. This indicator measures what percentage of all consumed aluminum is converted into aluminum hydroxide that adheres to the electrode surface. The lower the value, the more discharge products enter the electrolyte, and the less likely a passivation layer will form on the electrode surface.

[0077] The discharge performance analysis is as follows:

[0078] Depend on Figure 1 It can be seen that 1 mA / cm 2Under discharge conditions, the battery in Comparative Example 1 without additives had the lowest operating voltage. Adding polyaluminum chloride (Comparative Example 2) and sodium lactate (Comparative Example 3) alone both increased the battery operating voltage. In Example 1, where both polyaluminum chloride and sodium lactate were added, the battery operating voltage was further improved, superior to either using polyaluminum chloride or sodium lactate alone. The discharge curve was a nearly horizontal straight line with no significant fluctuations or attenuation throughout the process. After 90 hours of continuous discharge, the voltage remained at 1.28 V, indicating an extremely stable electrode / electrolyte interface and uniform aluminum anode dissolution. This demonstrates a synergistic effect between the additives polyaluminum chloride and sodium lactate, and their combined use can significantly improve the battery's operating voltage platform.

[0079] Table 1 shows 1 mA / cm 2 Electrochemical performance under discharge conditions. The blank electrolyte in Comparative Example 1 showed the lowest anodic utilization rate (35.80%), specific capacity, and specific energy. Adding either polyaluminum chloride (PAC) or sodium lactate alone improved anodic utilization, specific capacity, and specific energy; however, the PAC and sodium lactate combination in Example 1 achieved an anodic utilization rate of 60.89%, with optimal 90-hour long-term discharge voltage, specific capacity, and specific energy. This demonstrates that the PAC and sodium lactate combination can simultaneously achieve a high open-circuit potential, inhibit ineffective corrosion of the aluminum anode, and improve anodic utilization, significantly enhancing the overall discharge performance of the battery.

[0080] Table 1. Examples 1 and Comparative Examples 1-3 at 1 mA / cm 2 Down-discharge performance

[0081] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Anode utilization rate (%) 60.89 35.80 55.69 57.67 Discharge voltage (V) after 90 hours 1.28 1.22 1.28 1.26 Specific capacity (mAh / g) 1814.42 1066.77 1659.43 1718.43 Specific energy (mWh / g) 2294.51 1287.36 2109.73 2148.41

[0082] Figure 2 5mA / cm 2 The discharge voltage-time curves for Example 1 and Comparative Examples 1-3 are shown in Table 2, which presents the corresponding discharge performance test results. At 5 mA / cm²... 2 Under these conditions, the battery voltage of Comparative Example 1 without additives decayed rapidly, failing after approximately 16 hours and unable to complete a long discharge cycle. Comparative Example 2, with polyaluminum chloride added alone, exhibited a lower discharge voltage and significant voltage fluctuations. Comparative Example 3, with sodium lactate added alone, showed lower discharge voltage, anode utilization, effective specific capacity, and specific energy compared to Example 1. Example 1, with its combination of polyaluminum chloride and sodium lactate, achieved a discharge voltage of 5 mA / cm². 2 Under these conditions, the discharge curve remained stable, and the voltage remained at 1.15 V after 110 h of discharge. The anode utilization rate reached 68.81%, and the effective specific capacity and effective specific energy above 0.8 V were the best among all groups.

[0083] Based on the results of open circuit potential and anolyte adhesion aluminum ratio in Table 3, it can be seen that sodium lactate component mainly increases open circuit potential, while polyaluminum chloride component can significantly inhibit product adhesion; the combination of the two produces a synergistic effect, improving discharge performance.

[0084] Table 2. Examples 1 and Comparative Examples 1-5 at 5 mA / cm 2 Down-discharge performance

[0085] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Anode utilization rate (%) 68.81 50.00 51.33 66.40 Discharge voltage (V) after 110 h 1.15 0 0.85 0.95 Effective specific capacity (mAh / g) above 0.8 V 2050.60 1490.01 1529.73 1978.62 Effective specific energy (mWh / g) above 0.8 V 2323.41 1117.51 1300.27 2055.56

[0086] Table 3 Open circuit potential and percentage of anode-adhered aluminum in Example 1 and Comparative Examples 1-3

[0087] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Open circuit potential (V) 1.32 1.27 1.26 1.32 Percentage of aluminum adhered to the anode (%) 0.66 13.18 2.43 7.16

[0088] To determine the effective concentration range of the additives polyaluminum chloride and sodium lactate, this invention conducted boundary experiments with different amounts of polyaluminum chloride and sodium lactate added. Figure 3 It is evident that when the amount of sodium lactate added is low (Example 2, 0.03 g / L), the synergistic voltage-boosting effect of polyaluminum chloride and sodium lactate is weakened; when the amount of sodium lactate added is high (Example 3, 3 g / L), the initial operating voltage of the battery decreases. However, the voltage gradually increases and remains stable over operating time. When the amount of polyaluminum chloride added is low (Example 4, 0.05 g / L), the synergistic effect of the compound is significantly reduced; when the amount of polyaluminum chloride is increased to 5 g / L (Example 5), although the battery performance is slightly lower than that of the optimal example, it still has a significant voltage-boosting effect.

[0089] As can be seen from Table 4, at 1 mA / cm 2 When the concentrations of polyaluminum chloride and sodium lactate deviated from the optimal ratio, the specific capacity and specific energy both decreased, but compared with the blank control example 1, they still showed a significant performance improvement.

[0090] Table 4 Examples 1-5 and Comparative Example 1 at 1 mA / cm 2 Down-discharge performance

[0091] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Anode utilization rate (%) 60.89 56.17 56.36 48.51 53.43 35.80 Discharge voltage (V) after 90 hours 1.28 1.28 1.22 1.25 1.27 1.22 Specific capacity (mAh / g) 1814.42 1673.99 1679.38 1445.56 1592.24 1066.77 Specific energy (mWh / g) 2294.51 2105.42 2002.35 1751.84 1947.92 1287.36

[0092] Depend on Figure 4 As can be seen, Examples 1, 2, 4, and 5 are at 5 mA / cm 2 The voltage remained relatively high throughout the process, and the curve was generally stable. In Example 3, the voltage was acceptable in the early stage of discharge, but it dropped significantly after 80 hours, and the stability deteriorated. When the sodium lactate content was high, defects were exposed under long-term high-current conditions.

[0093] As can be seen from Table 5, Example 5 at 5 mA / cm 2The electrochemical performance is excellent, with effective specific energy and effective specific capacity even slightly higher than those of Example 1; however, according to Table 6, the anodic adhesion rate is relatively high. Nevertheless, Examples 1-5 still show a significant performance improvement compared to the blank control example 1.

[0094] Table 5 Examples 1-5 and Comparative Example 1 at 5 mA / cm 2 Down-discharge performance

[0095] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Anode utilization rate (%) 68.81 61.54 69.76 67.44 71.12 50.00 Discharge voltage (V) after 110 h 1.15 1.11 0.99 1.09 1.16 0 Effective specific capacity (mAh / g) above 0.8 V 2050.60 1833.83 2078.84 2009.78 2119.49 1490.01 Effective specific energy (mWh / g) above 0.8 V 2323.41 2089.68 2182.62 2272.72 2421.74 1117.51

[0096] Table 6. Open circuit potential and percentage of anode-adhered aluminum in Examples 1-5 and Comparative Example 1

[0097] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Open circuit potential (V) 1.32 1.34 1.32 1.33 1.30 1.27 Percentage of aluminum adhered to the anode (%) 0.66 9.68 6.11 3.67 7.14 13.18

[0098] To verify the substitutability of component A, the sodium lactate additive in Example 1 was replaced with potassium lactate, zinc lactate, and lithium lactate, which have similar structures, respectively, resulting in Examples 6-8. Comparative Example 2, which only added polyaluminum chloride and did not contain component A, was set as a reference. The samples were tested at 1 mA / cm². 2 5 mA / cm 2 Discharge tests were conducted at current density.

[0099] Depend on Figure 5 It can be seen that 1 mA / cm 2 In Examples 1 and 6, the voltage platforms were the highest and most stable; in Examples 7 and 8, the voltages were lower than those in Comparative Example 2, but still showed a performance improvement compared to the blank Comparative Example 1.

[0100] As shown in Table 7, Example 6, which replaced sodium lactate with potassium lactate, had the same discharge voltage at the end of 90 h as Example 1, but slightly lower anode utilization, specific capacity, and specific energy than Example 1, and better than Comparative Example 2, which did not contain component A. Example 8, which replaced sodium lactate with lithium lactate, also had good discharge performance. Example 7, which replaced sodium lactate with zinc lactate, showed a significant decrease in various electrochemical properties.

[0101] Table 7 Examples 1, 6-8 and Comparative Example 1 at 1 mA / cm 2 Down-discharge performance

[0102] Example 1 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Anode utilization rate (%) 60.89 57.22 40.35 54.64 35.80 55.69 Discharge voltage (V) after 90 hours 1.28 1.28 1.24 1.25 1.22 1.28 Specific capacity (mAh / g) 1814.42 1704.35 1202.51 1628.76 1066.77 1659.43 Specific energy (mWh / g) 2294.51 2168.72 1477.85 2035.14 1287.36 2109.73

[0103] Depend on Figure 6 It can be seen that at 5 mA / cm 2 Below, the blank control example 1 failed rapidly. Based on the data in Table 8, Example 8 showed higher effective specific capacity and effective specific energy; Example 6 exhibited higher anode utilization, but the voltage decreased at the end of discharge; Example 7 showed a significant drop in discharge voltage over time.

[0104] Based on the data in Table 9, after the original additive sodium lactate in Example 1 was replaced with potassium lactate (Example 6) and lithium lactate (Example 8), the proportion of aluminum adhering to the anode increased significantly, but compared with the blank control example 1, it still had the effect of improving anode adhesion.

[0105] Table 8. Examples 1, 6-8, and Comparative Example 1 at 5 mA / cm 2 Down-discharge performance

[0106] Example 1 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Anode utilization rate (%) 68.81 71.93 53.53 72.26 50.00 51.33 Discharge voltage (V) after 110 h 1.15 1.09 0.86 1.17 0 0.85 Effective specific capacity (mAh / g) above 0.8 V 2050.60 2143.61 1595.34 2513.44 1490.01 1529.73 Effective specific energy (mWh / g) above 0.8 V 2323.41 2378.41 1466.57 2518.62 1117.51 1300.27

[0107] Table 9. Open circuit potential and percentage of anode-adhered aluminum in Examples 1-5 and Comparative Example 1

[0108] Example 1 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Open circuit potential (V) 1.32 1.25 1.23 1.29 1.27 1.26 Percentage of aluminum adhered to the anode (%) 0.66 9.45 2.29 6.14 13.18 2.43

[0109] To verify the substitutability of component B, the additive polyaluminum chloride in Example 1 was replaced with polyaluminum sulfate, polyaluminum ferric silicate, polyaluminum ferric chloride, and polyaluminum silicate sulfate, respectively, resulting in Examples 9-12. Comparative Example 3, which only added polyaluminum chloride and did not contain component A, was set as a reference. The samples were tested at 1 mA / cm². 2 5 mA / cm 2 Discharge tests were conducted at current density.

[0110] Depend on Figure 7 It can be seen that 1 mA / cm 2 Below, the voltage plateaus of Examples 1 and 9 are the highest; Examples 10 and 11 are the next highest; and the voltage plateau of Comparative Example 4 is significantly lower.

[0111] As shown in Table 10, Example 9, which replaced polyaluminum chloride with polyaluminum sulfate, had the same discharge voltage at the end of 90 h as Example 1, but slightly lower anode utilization, specific capacity, and specific energy than Example 1. Its performance was better than that of Comparative Example 3, which contained only sodium lactate. Examples 10 and 11, which replaced polyaluminum ferric silicate and polyaluminum ferric chloride, also had good discharge performance. Comparative Example 4, which replaced polyaluminum silicate sulfate, showed a significant decrease in various electrochemical properties.

[0112] Table 10 Examples 1, 9-11 and Comparative Examples 1, 3, 4 at 1 mA / cm 2 Down-discharge performance

[0113] Example 1 Example 9 Example 10 Example 11 Comparative Example 1 Comparative Example 3 Comparative Example 4 Anode utilization rate (%) 60.89 59.71 58.44 57.92 35.80 57.67 42.17 Discharge voltage (V) after 90 hours 1.28 1.28 1.26 1.26 1.22 1.26 1.23 Specific capacity (mAh / g) 1814.42 1779.34 1741.02 1725.51 1066.77 1718.43 1254.68 Specific energy (mWh / g) 2294.51 2247.68 2193.69 2169.14 1287.36 2148.41 1543.26

[0114] Depend on Figure 8 It can be seen that at 5 mA / cm 2 Under these conditions, the blank control example 1 failed rapidly. Examples 9-11 maintained stable discharge; the voltage of control example 4 dropped directly during discharge and failed; the voltage of control example 3, which did not contain component B, decreased significantly at the end of the discharge process.

[0115] As shown in Table 11, Example 9 exhibits higher anode utilization and effective specific capacity; however, the final voltage drops to 1.08 V. Comparative Example 4, at 5 mA / cm²... 2 Although the anode utilization rate was acceptable, the voltage dropped to zero midway, indicating failure. Therefore, polyaluminum silicate sulfate cannot be considered an equivalent substitute for polyaluminum chloride. In Comparative Example 3, the voltage at the end was only 0.95 V, showing severe voltage decay. This further demonstrates that sodium lactate alone, lacking component B, has a significant weakness in high-current, long-cycle stability.

[0116] Based on the data in Table 12, in Example 1, the proportion of aluminum adhering to the anode was as low as 0.66% when the original additive polyaluminum chloride was compounded with sodium lactate. After replacing it with polyaluminum sulfate, polyaluminum ferric silicate, and polyaluminum ferric chloride, the proportion of aluminum adhering to the anode increased significantly. Compared with the blank control example 1, polyaluminum sulfate almost lost its ability to inhibit anode adhesion and failed directly under high current, thus failing to achieve the complete technical effect of the present invention.

[0117] Table 11 Examples 1, 9-11 and Comparative Examples 1, 3, 4 at 5 mA / cm 2 Down-discharge performance

[0118] Example 1 Example 9 Example 10 Example 11 Comparative Example 1 Comparative Example 3 Comparative Example 4 Anode utilization rate (%) 68.81 67.34 65.87 64.21 50.00 66.40 60.52 Discharge voltage (V) after 110 h 1.15 1.08 1.13 1.11 0 0.95 0 Effective specific capacity (mAh / g) above 0.8 V 2050.60 2210.56 1949.41 1900.73 1490.01 1978.62 1803.55 Effective specific energy (mWh / g) above 0.8 V 2323.41 2457.35 2214.83 2202.74 1117.51 2055.56 1541.92

[0119] Table 12 Open circuit potential and percentage of anode-adhered aluminum in Examples 1, 9-11 and Comparative Examples 1, 3, and 4

[0120] Example 1 Example 9 Example 10 Example 11 Comparative Example 1 Comparative Example 3 Comparative Example 4 Open circuit potential (V) 1.32 1.28 1.33 1.32 1.27 1.32 1.35 Percentage of aluminum adhered to the anode (%) 0.66 2.64 5.32 6.04 13.18 7.16 14.06

[0121] In summary, the neutral electrolyte of this invention, through the synergistic effect of component A (hydroxycarboxylic acid metal salt) and component B (polymerized inorganic aluminum salt), not only achieves dual regulation of in-situ suppression and electrostatic repulsion dispersion of aluminum hydroxide, the aluminum anolyte discharge product, but also achieves a high discharge voltage plateau that remains stable over a wide current density range, effectively suppressing anolyte adhesion and significantly improving the effective specific energy. In particular, the polyaluminum chloride-sodium lactate electrolyte additive of this invention can significantly improve the discharge voltage plateau, stability, and effective specific energy of aluminum-air batteries over a wide current density range, significantly suppress anolyte adhesion, effectively delay the electrode passivation process, and achieve a balanced optimization of performance.

[0122] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A neutral electrolyte for aluminum-air batteries, characterized in that, The electrolyte comprises a basic electrolyte, a composite additive, and a solvent; the composite additive is composed of a compound of component A and component B. Component A is a solid powder / particle or aqueous solution of a metal salt of hydroxycarboxylic acid; Component B is a polymeric inorganic aluminum salt.

2. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, The hydroxycarboxylic acid metal salt in component A is an alkali metal salt and / or a transition metal salt of lactic acid.

3. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, Component A is at least one of sodium lactate, potassium lactate, zinc lactate, and lithium lactate.

4. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, Component B is at least one of polyaluminum chloride, polyaluminum sulfate, polyaluminum ferric silicate, and polyaluminum ferric chloride.

5. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, Component A is sodium lactate; component B is polyaluminum chloride.

6. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, Based on the total volume of the neutral electrolyte for the aluminum-air battery, the amount of component A added is 0.03–3 g / L (based on the effective mass of the hydroxycarboxylic acid metal salt), and the amount of component B added is 0.05–5 g / L.

7. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, The basic electrolyte is sodium chloride and / or potassium chloride.

8. The neutral electrolyte for aluminum-air batteries as described in claim 1, characterized in that, Based on the total weight of the neutral electrolyte for the aluminum-air battery, the content of the basic electrolyte is 1 to 3 mol / L.

9. A method for preparing a neutral electrolyte for an aluminum-air battery as described in any one of claims 1 to 8, characterized in that, The preparation method includes the following steps: adding component A and component B to an aqueous solution of a basic electrolyte, stirring or sonicating to dissolve, thereby obtaining the neutral electrolyte for aluminum-air batteries.

10. An application of a neutral electrolyte for aluminum-air batteries, characterized in that, The aluminum-air battery is obtained by adding the neutral electrolyte of the aluminum-air battery as described in any one of claims 1 to 9 into the cavity of the aluminum-air battery composed of an aluminum anode plate and a cathode plate.

Citation Information

Patent Citations

  • Electrolyte and aluminum air battery

    CN113851665A

  • A neutral electrolyte aluminum-air battery and its preparation method

    CN116190866B

  • Neutral aluminum-air battery electrolyte based on composite additive

    CN117335060A

  • High-discharge-potential neutral aluminum air battery electrolyte based on iron ion additive

    CN120016029A